Perception of graduates from the technical course in Agroecology at IFAL regarding the importance of work safety teaching (Research, Society and Development, 2022)
The objective of this study was to evaluate the perception of graduates about the discipline that addresses occupational safety in the technical course in Agroecology at IFAL Campus Maragogi. The research was carried out with students who graduated from that course through the application of a questionnaire containing 15 questions and prepared through the Google Forms platform, which was submitted via email, social network, and WhatsApp with authorization from the department responsible for the academic record. The period studied was between the years 2015 to 2021. 25 questionnaires were analyzed. Most of the graduating students who answered the questionnaire showed considerable acuity regarding the topic of safety at work in the Technical Course in Agroecology. The research also revealed that the graduating students have a preventive notion regarding the risks commonly found in rural areas.